Distribution and Phenotypic Characteristics of Warmblood Horses Breed for Equestrian Sports - Paksoy, Y; Güney, MÇ; Koluman, N (Journal of the Hellenic Veterinary Medical Society, 2025)
Equestrian sports are widely practiced worldwide and the physical characteristics of different horse breeds play an important role in these activities. In this study, the cidago heights of half-blood horses bred in equestrian sports within the Turkish Equestrian Federation were investigated in relation to breed, gender, frost and age. A total of 11 stallions, 48 mares and 85 geldings representing 4 breeds (German, Dutch, French, Belgian) and 4 age groups (5-9 years, 10-14 years, 15-19 years and 20 years and over) were included in the study. Information about the horses was obtained from pedigree records provided by the Turkish Equestrian Federation. The cidago measurements of the horses were measured by the researchers on a flat surface from the left side of each horse with a measuring stick. The minimum, maximum and mean values of the cidago height of the horses were found to be 162.46 cm, 183.93 cm and 172.33 cm, respectively. The highest mean Cidago height was observed in Belgian breed horses (173,80 cm), horses aged 5-9 years (172,86 cm), stallions (173,54 cm) and horses with bay color (173,15 cm). Statistical analysis revealed that the effect of the breed on the height of the fetlock was significant (P<0.05), while the effects of age, sex and frost were insignificant (P>0.05). According to the results of this study, it further strengthens the conclusion that breed is a factor affecting conformation in half-breed horses. Thanks to this study, some important characteristics of horses used in equestrian sports have been revealed.